What is The Effect of Early Enteral Nutrition on Mortality in Critically Ill Patients Receiving Vasopressor Support? : A Systematic Review - Landong Sijabat; Raka Jati Prasetya; Mutia Juliana (The International Journal of Medical Science and Health Research, 2026)
Background: The effect of early enteral nutrition (EEN) on mortality in critically ill patients requiring vasopressor support remains debated due to conflicting trial results. Methods: This systematic review synthesized data from 80 studies (2003-2025), including landmark RCTs (NUTRIREA-2, NUTRIREA-3) and large observational cohorts, focusing on mortality, vasopressor dose-response, enteral tolerance, and safety. Results: EEN did not reduce 28-day or 90-day mortality in patients with severe shock (norepinephrine ≥0.3 µg/kg/min) in major RCTs [1,2]. However, a clear dose-response relationship was identified: EEN significantly reduced mortality at low (<0.1 µg/kg/min) and medium (0.1-0.3 µg/kg/min) norepinephrine doses but not at high doses (≥0.3 µg/kg/min) [3]. Benefits were seen in transient shock (resolving <24h) but not persistent shock [4]. High-calorie EEN increased gastrointestinal complications, including vomiting (HR 1.89) and bowel ischemia (HR 3.84) [1], while low-calorie feeding (6 kcal/kg/day) reduced these risks [2]. Discussion: The effect of EEN on mortality is highly context-dependent. The lack of benefit in trials like NUTRIREA-2/3 is explained by enrollment of patients on high-dose vasopressors and use of immediate full-dose feeding—a strategy now considered harmful. Observational benefits likely reflect hemodynamic stability at feeding initiation. A safe approach includes starting trophic EEN (6-15 kcal/kg/day) after initial resuscitation when vasopressor doses are stable and ≤0.3 µg/kg/min, with gradual advancement. Conclusion: EEN does not reduce mortality in patients on high-dose vasopressors (≥0.3 µg/kg/min norepinephrine) but may improve survival in those on low-to-moderate doses with transient shock. Clinical practice should shift from rigid timing to hemodynamic-guided, gradual feeding.